Transformative process: Crafting imines from nitrobenzene and benzyl alcohol coupling with cerium oxide modified mesoporous SBA-15 - Soumini Chandralayam; Sugunan Sankaran (Teknomekanik, 2024)
A low-cost and eco-friendly cerium oxide modified mesoporous SBA-15 catalyst was developed by wet impregnation. It enables sequential oxidation of benzyl alcohol and reduction of nitrobenzene, followed by imine formation in a single and solvent-free system. Characterization confirms homogeneous cerium oxide dispersion, high stability, and enhanced redox properties. The optimized catalyst demonstrates excellent conversion and selectivity, attributed to the mesoporous SBA support, acidic properties, and cerium's redox functionality. Elevated temperatures enhance benzyl alcohol dehydration and hydrogen diffusion, facilitating intermediate aniline formation by a borrowing-hydrogen mechanism and followed by imine synthesis. It eliminates solvents, reduces byproducts, and achieves high atom economy and renewability. It presents a significant advance in sustainable catalysis. The catalyst's robustness and ease of recovery strengthen its practicality for repeated cycles. The findings provide a scalable and energy-efficient solution for greener imine synthesis with potential applications in industrial processes requiring efficient and eco-friendly chemical production. It ensures minimal environmental impact and offers a cost-effective pathway for high-value chemical synthesis. This study supports the SDGs by promoting sustainable industrial practices through the development of a low-cost and eco-friendly catalyst that reduces environmental impact, enhances energy efficiency, and contributes to greener chemical production.